The Personal Librarian : Enhancing the Student Experience. - Moniz, Richard (American Library Association, 2014)
Enter the Personal Librarian, a flexible concept that focuses on customizing information literacy by establishing a one-on-one relationship between librarian and student from enrollment through graduation.